Upaya Meningkatkan Hasil Belajar Matematika Materi Sudut Siku-Siku Melalui Pendekatan Pakem pada Siswa Kelas VI Semeter I SD Negeri 4 Muara Dua Tahun 2018/2019 - Halimatussakdiah Halimatussakdiah (Keguruan, 2021)
This study was conducted in SD Negeri 4 Muara Dua, Class VI semester I with a total of 27 students. Data collection techniques used are observation, and tests. The results of initial observations in SD Negeri 4 Muara Dua, in learning mathematics in Class VI Materials for Right-angled Angles obtained data that students still have not mastered the material. This is evidenced by the value of student learning outcomes at the end of the lesson that has not reached the KKM. To overcome these problems, a learning improvement is needed, by applying the PAKEM approach as an approach to influencing student interaction patterns and aiming to improve academic mastery. The results showed that applying the PAKEM approach could improve the process and student learning outcomes in the Mathematics subject for right angles. This can be seen in student learning completeness in the first cycle, which is 77.78% and increases to 88.89% in the second cycle. Based on the results of the study, it can be concluded that the PAKEM approach can improve student learning outcomes in Right-angled Materials. Thus, teachers can apply the PAKEM approach so that mathematics learning can increase student activity in learning.